Racism Postrace - Gray, Herman, 1950-; Banet-Weiser, Sarah, 1966-; Mukherjee, Roopali (Book collections on Project MUSE., 2019)
With the election of Barack Obama, the idea that American society had become postracial-that is, race was no longer a main factor in influencing and structuring people's lives-took hold in public consciousness, increasingly accepted by many. The contributors to 'Racism Postrace' examine the concept of postrace and its powerful history and allure, showing how proclamations of a postracial society further normalize racism and obscure structural antiblackness. They trace expressions of postrace over and through a wide variety of cultural texts, events, and people, from sports (LeBron James's move to Miami), music (Pharrell Williams's "Happy"), and television (The Voice and HGTV) to public policy debates, academic disputes, and technology industries. Outlining how postrace ideologies confound struggles for racial justice and equality, the contributors open up new critical avenues for understanding the powerful cultural, discursive, and material conditions that render postrace the racial project of our time